(untitled) (Revista de Artes Marciales Asiáticas, 2014)
The present report provides a short description of a conference entitled "First International Research Conference on Weaponology in Kyiv, Ukraine". It was the first scientific conference dedicated to the study of historical arms and armor in Ukraine. A number of international experts in the field of historical arms and armor were invited to the conference. Each researcher had been asked to provide a short and a long article on a specific research subject. The short articles were published as a short essay in a peer-review booklet that was handed out before the start of the conference. The long articles will be published together as a large book in future.